Metronidazole-induced Neurotoxicity: Case Report - Cámara-Reyes, Ramon Rolando (2025)
Metronidazole-induced neurotoxicity is an uncommon but underestimated complication in patients with prolonged exposure. We present the case of a 67-year-old male who presented with ataxia and seizures after receiving metronidazole and ceftriaxone for 65 days. The brain MRI showed typical lesions in the dentate nucleus, mesencephalon, and corpus callosum. Clinical and radiographic improvements were observed after stopping the antimicrobial. This case report emphasizes the importance of considering this entity in the differential diagnosis of neurologic derangement during prolonged antibiotic therapy, identifies MRI as a key diagnostic tool, and increases awareness to minimize serious adverse effects.